Impact of a nationwide school policy on body mass index in Danish school children: An interrupted time series analysis - Natascha H. Pedersen; Anders Grøntved; Niels C. Møller; Birgit Debrabant; Kristian T. Larsen; Jan C. Brønd; Jens Troelsen; Søren Brage; Jacob v B. Hjelmborg; Niels Wedderkopp; Lars B. Christiansen; Sofie R. Mortensen; et al. (Public Health in Practice, 2024)
Objectives: A new school policy mandating 45 min physical activity daily during school was introduced in Denmark in 2014. We aimed to evaluate the effect of this policy on BMI in school-aged children. It was hypothesized that the school policy would decrease BMI, especially in the obese fraction of the population (90th percentile BMI). Study design: This register-based study was conducted as a natural experiment. Methods: Analyses were based on data from The National Child Health Register that contains nationwide data on height and weight from mandatory preventive health examinations completed by school nurses or medical doctors during pre-preparatory classes (0th-3rd grade) and lower secondary education (7th-9th grade). A total of 401,517 children were included in the analyses with annual repeated cross-sectional data covering the period from 2012 to 2018. The effect of the school policy was evaluated using an interrupted time series approach comparing pre- and post-policy slopes in BMI, stratified by sex and age-group. Results: In boys, no significant differences were observed in mean BMI slopes from pre-to post-policy in either age-group. In girls, post-policy slopes were significantly higher compared to pre-policy in both age-groups (0th-3rd grade: β:0·034 kg/m2, 95%-CI: (0·024; 0·043), p-value: <0·001; 7th-9th grade: β:0·066 kg/m2, 95%-CI: (0·028; 0·103), p-value: 0·001). No significant differences in slopes were observed in BMI at the 90th percentile from pre-to post-policy for both sexes and across both age-groups. Adjustment for leisure-time physical activity as a potential time-varying confounder did not alter the findings. Conclusions: In conclusion, we did not detect a significant decrease in BMI levels among school-aged children following the introduction of a nationwide school policy specifying daily physical activity in school. If anything, a small positive change in BMI was observed in girls. More research is needed to understand whether structural changes similar to this requirement are able to prevent overweight and obesity in children and adolescents.